Strategies to support high school students’ reading comprehension in the english language (2004)
Teachers are often concerned about the low reading level of their students in both English and Spanish. One way to solve this problem is by using reading strategies. Promoting the development of reading competences in English will offer the students tools that allow them to comprehend texts and will contribute to a closer relation with the second language culture. This article reports on a study carried out when doing my teaching practice in a public high school in Bogotá, Colombia, in 2002. The main objective of my research project was to support the development of eleventh graders’ reading comprehension competence in English. Hence, I refer to the group’s views on English reading comprehension, their handling of strategies to develop reading competence in English and their progress after having applied those strategies. Key words: Foreign Language-Teaching, Reading Strategies El bajo nivel de lectura en los estudiantes de inglés y español es una de las preocupaciones comunes de los docentes. Una forma de solucionar este problema es a través del uso de estrategias de lectura. De tal manera, promover el desarrollo de competencias lectoras en los estudiantes de inglés les ofrecerá herramientas que les permitirán comprender los textos y contribuirá a crear una relación más cercana entre ellos y la cultura de la segunda lengua. Este artículo reporta un estudio llevado a cabo durante mi práctica docente en una escuela pública de Bogotá, Colombia, en el año 2002. El objetivo principal de mi proyecto de investigación fue apoyar el desarrollo de la competencia en comprensión de lectura en el idioma inglés en estudiantes de undécimo grado. Por lo tanto, menciono los puntos de vista de los estudiantes sobre la comprensión de lectura, la forma como utilizan las estrategias para desarrollar esta competencia en inglés y su proceso después de su acercamiento a la comprensión lectora a través del uso de las mismas. Palabras claves: Lengua Extranjera-Enseñanza, Estrategias de Lectura